Travessia no teatro, travessias na performance: territórios de investigação e criação no IFMA Campus Barra do Corda - Pinheiro, Anderson da Silva (2016)
This research, inserted in the line of research teaching Processes, Learning and Mediation in Arts, it is proposed to reflect on artistic and pedagogical practices in performance developed in the Campus Barra do Corda Federal Institute of Education, Science and Technology of Maranhão - IFMA. In written text, the description of educational processes, dialogue with literature and autobiographical narrative constituted the research proposal in an attempt to highlight theoretical and practical possibilities of the insertion of performance in educational situations. The field was given in the context of work of basic education and focused, in particular, the reflection on the process of creation and circulation performance entitled Status: on line, the Center TRAVESSIA for Research in Performing Arts, formed by high school students Campus Barra do Corda of IFMA. The performance was designed in order to provide students new ways of understanding the art in view of the contemporary world, the time that the research showed the relationship between art and education.